IMPROVE MARKETING PERFORMANCE THROUGH MARKET SENSING CAPABILITY, DYNAMIC CAPABILITIES, AND NEW PRODUCT DEVELOPMENT - Nurul Komaryatin; M. Rifqy Roosdhani; Samsul Arifin; Ali; Nurul Huda (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The worsening sales trend of Jepara furniture exporters as a result of substandard marketing performance is the driving force for this research. Currently, a company's ability to improve its marketing performance is very important because it shows how well the company can meet its sales targets in the market. An effective method for identifying problems that impact a company's competitiveness and sustainability is to examine its marketing performance and the factors that influence that marketing performance. This study shows market sensing capabilities, dynamic capabilities, and new product development that can be used by Jepara furniture exporters to improve their marketing performance. This survey involved 60 respondents and used quantitative techniques. Purposive sampling is used in the sampling procedure. The research utilizes multiple linear regression analysis for data examination. Research findings show that market sensing capability, dynamic capabilities, and new product development all influence marketing performance. In this research, expanding market sensing capabilities, dynamic capabilities and new product development are recommended for Jepara furniture export companies. Thus, the furniture export business in Jepara will have better marketing performance.